Interior design : - Binggeli, Corky (John Wiley & Sons, 2007)
Interior Design: A Survey provides a comprehensive overview of the field of interior design and the many areas of expertise you'll need for a successful career as an interior designer. Starting off with a fascinating tour of the history of interior design through the ages, this guide covers the process of interior design—the development of a design concept, analysis of built spaces, programming and functional relationships, space planning, design development presentation, and more